Decolonizing the Anthropocene: Reading Charles de Lint’s "Widdershins" - Łaszkiewicz, Weronika (Acta Neophilologica, 2020)
The aim of this paper is to examine Charles de Lint’s novel Widdershins(2006), whose main theme is an interspecies war for the American land. The paper demonstrates how, by exploring the themes of Indigenous suffering, belief in species interconnectedness, reverence for the natural world, and approach to trauma, the novel participates in the deconstruction of colonial structures present in the concept of the Anthropocene. The paper also engages de Lint’s novel in a dialogue with the studies on the Anthropocene to prove that, by providing its readers with alternative modes of thinking, fantasy fiction can contribute to the cognitive change required to save our planet from human-wrought destruction.